2023
DOI: 10.3390/catal13071085
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Investigation and Machine Learning-Based Prediction of Decolorization of Wastewater by Using Zeolite Catalyst in Electro-Fenton Reaction

Atef El Jery,
Moutaz Aldrdery,
Ujwal Ramesh Shirode
et al.

Abstract: The shortage of water resources has caused extensive research to be conducted in this field to develop effective, rapid, and affordable wastewater treatment methods. For the treatment of wastewater, modern oxidation techniques are desirable due to their excellent performance and simplicity of implementation. In this project, wet impregnation and the hydrothermal technique were applied to synthesize a modified catalyst. Different analysis methods were used to determine its characteristics, including XRD, BET, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Furthermore, the fundamental association between catalyst fingerprint properties and pollutant degradation is difficult to quantify. 40 Researchers can utilize advanced analytical techniques, such as simulations and tests, to quantify the fingerprint properties of catalysts and their impact on pollutant degradation, thus addressing this problem. When combined with experimental data, data-driven machine learning models can help researchers identify natural links between the catalyst properties and the rate at which contaminants in water resources break down.…”
Section: Challenges and Solutions In Predicting Catalytic Degradation...mentioning
confidence: 99%
“…Furthermore, the fundamental association between catalyst fingerprint properties and pollutant degradation is difficult to quantify. 40 Researchers can utilize advanced analytical techniques, such as simulations and tests, to quantify the fingerprint properties of catalysts and their impact on pollutant degradation, thus addressing this problem. When combined with experimental data, data-driven machine learning models can help researchers identify natural links between the catalyst properties and the rate at which contaminants in water resources break down.…”
Section: Challenges and Solutions In Predicting Catalytic Degradation...mentioning
confidence: 99%
“…The SMT removal by the M@BN-C cathode was measured at different pH conditions, and it was observed that the SMT removal decreased as the pH increased (Figure 7a-c). This decline could be attributed to the favorable production of • OH under acidic conditions, which facilitated pollutant degradation [43,44]. In addition, higher leaching of transition metal resulted in the generation of more free • OH and less 1 O 2 .…”
Section: The Effect Of Ph On Catalytic Performance By M@bn-cmentioning
confidence: 99%
“…Also, in order to further prevent overfitting, dropouts were utilized in some hidden layers. These techniques help prevent the model from overfitting on certain features and enhance its ability to generalize to new data [84][85][86][87][88][89][90][91]. To add more insight on the selection of the ANN model, a comparison between the predictive capabilities of the ANN and random forest (RF) is performed.…”
Section: Artificial Neural Networkmentioning
confidence: 99%